"Refractory Metal, RM – Wrap": A tailorable, pressure-less joining technology. Issue 4 (March 2019) - Gianchandani, Pardeep Kumar; Casalegno, Valentina; Salvo, Milena; Ferraris, Monica; Dlouhý, Ivo
Abstract: The RM-wrap (RM = Refractory Metal) is a pressure-less, versatile and tailorable joining process: it consists of wrapping Si foils inside a refractory metal wrap (i.e., Mo, Nb, Ta) in order to prevent molten silicon from leaking outside the joined region and infiltrating the facing materials during the joining process. RM-wrap (RM = Mo, Nb, Ta) has been successfully applied to join C/SiC composites in this work: optimized joining treatment consisted of heating to 1450 °C with a heating rate of 1000 °C/h followed by a dwell time of 5 min in a non-reactive environment of Argon flow. The joints were characterized by morphological analysis and lap shear tests at room temperature and 1000 °C. Microscopical analysis revealed an in-situ formed composite joint consisting of a silicon matrix reinforced with silicides of the refractory metals. Joining material exhibited continuous and cracked free bonding with C/SiC irrespective of composite fibre orientation. Joints lap shear strength values at 1000 °C were higher than at room temperature, probably due to the brittle to ductile transition (BTDT) of silicon and silicides. Vickers microhardness on refractory metal disilicides measured inside the joints showed a trend similar to their mechanical strength, with higher lap shear strength and hardness for Mo-Wrap and lower for Ta-wrap joints.